Knowledge of Orthostatic Hypotension among Doctors Working at a Tertiary Care Hospital in Sri Lanka - Shehan Silva; Warsha De Zoysa; Udayangani Ramadasa; Jegarajah Indrakumar (Journal of the Indian Academy of Geriatrics)
Introduction: Orthostatic hypotension (OH) is prevalent in older adults as well as in individuals with chronic medical conditions and those taking specific medications. Despite its significance, OH remains underdiagnosed and poorly managed, partly due to limited training and awareness among doctors. Aims and Objectives: This study aims to assess the knowledge and practices of medical officers regarding OH at Colombo South Teaching Hospital, Sri Lanka. Materials and Methods: A descriptive cross-sectional study was conducted among 200 registered medical officers. Data were collected through a pretested, self-administered questionnaire addressing demographic details, knowledge of OH diagnostic protocols, symptoms, and management strategies. Results: There were 200 medical officers, 22% of whom were consultants. The mean participant age was 48.2 years, with 58% being male. Knowledge of systolic and diastolic blood pressure changes was significantly higher among consultants (63.63% and 79.54%, respectively) (P < 0.01) compared to medical officers (35.25% and 38.46%, respectively) (P < 0.01). However, knowledge of proper OH measurement protocols, including the timing of blood pressure readings, was poor in both groups, with no significant difference (P > 0.05). Awareness of common OH symptoms such as dizziness and falls was high, but less common symptoms (e.g. weakness and fatigue) were poorly recognized. Knowledge of pharmacological treatment options was insufficient in both groups. Conclusion: This study underscores the need for enhanced training and education on OH in Sri Lanka, particularly regarding diagnostic protocols, symptom recognition, and management strategies. Incorporating these could bridge the knowledge gap and improve patient outcomes, reducing the risk of falls and associated morbidities in older adults.